(untitled) (Práxis Educativa, 2009)
This paper discusses the school management and how the administration carries in its contents factors permeates by a worldview, society and education. These views influence the understanding of the reality and create possibilities of interventions in this reality. In this sense, to analyze the education management implies to reflect about education policies since there a closely relationship among them and the administrations changes the aims and goals of education in actions, implementing in the schools the guidelines established. The paper intends to identify the levels of participations of the students, parents, and school staff, as well as to discuss the tactics that these social actors create to intervene in the bureaucratic mechanism established in the schools and by the educational policies as movement of resistance to the power instituted. The paper assume that the fact that the researcher is involved in the dynamic or dialectical circle (theory/practice) allows to better understand the difficulties, problems, contradictions, partnerships, encounters and disengagement of social actors and subjects of the research. Keywords: Educational management. Schools day-to-day operations. Participation. Culture.